Influenza A virus segments five and six can harbor artificial introns allowing expanded coding capacity. - Heather M Froggatt (Public Library of Science (PLoS), 2021)
Influenza A viruses encode their genomes across eight, negative sense RNA segments. The six largest segments produce mRNA transcripts that do not generally splice; however, the two smallest segments are actively spliced to produce the essential viral proteins NEP and M2. Thus, viral utilization of RNA splicing effectively expands the viral coding capacity without increasing the number of genomic segments. As a first step towards understanding why splicing is not more broadly utilized across genomic segments, we designed and inserted an artificial intron into the normally nonsplicing NA segment. This insertion was tolerated and, although viral mRNAs were incompletely spliced, we observed only minor effects on viral fitness. To take advantage of the unspliced viral RNAs, we encoded a reporter luciferase gene in frame with the viral ORF such that when the intron was not removed the reporter protein would be produced. This approach, which we also show can be applied to the NP encoding segment and in different viral genetic backgrounds, led to high levels of reporter protein expression with minimal effects on the kinetics of viral replication or the ability to cause disease in experimentally infected animals. These data together show that the influenza viral genome is more tolerant of splicing than previously appreciated and this knowledge can be leveraged to develop viral genetic platforms with utility for biotechnology applications.